Effect of diet-induced weight loss on iron status and its markers among young women with overweight/obesity and iron deficiency anemia: a randomized controlled trial - Alshwaiyat, Naseem Mohammad; Ahmad, Aryati; Al-Jamal, Hamid Ali Nagi (Frontiers in Nutrition, 2023)
Obesity and iron deficiency are prevalent health problems that affect billions of people all over the world. Obesity is postulated to relate to iron deficiency via reduced intestinal iron absorption due to increased hepcidin level, which is mediated by chronic inflammation. Weight loss in individuals with overweight or obesity and iron deficiency anemia is believed to be associated with an improvement in iron markers however the evidence from clinical trials is scarce. Using a randomized controlled trial with two parallel arms study design, this study was conducted to evaluate the effect of diet-induced weight loss on iron status among young women with overweight/obesity and iron deficiency anemia. A total of 62 women were recruited and randomized into weight loss intervention and control group for three months. Anthropometric measurements and clinical markers were measured at baseline and end of the trial. There was a significant decrease (P ˂ 0.001) in body weight of the intervention group (-7.4 ± 2.7 kg) that was associated with a significant increase in iron and hematological profiles (P ˂ 0.01). High sensitivity C-reactive protein (P ˂ 0.001) and serum hepcidin (P ˂ 0.001) were decreased significantly. In conclusion, our findings indicate that diet-induced weight loss among participants was associated with an improvement in iron status and its related clinical markers. Clinical trial registration number: TCTR20221009001.